2016
DOI: 10.2169/internalmedicine.55.5218
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Disparity between Fingers after Cold-water Immersion of Hands: A Useful Indicator of Disturbed Peripheral Circulation in Raynaud Phenomenon Patients

Abstract: Objective To devise an effective method to assess the peripheral circulation using an infrared thermographic analysis. Methods Sequential measurements of the skin temperature before and after cold-water immersion of the hands were analyzed by a thermographic examination in healthy controls and patients diagnosed to have Raynaud phenomenon (RP). The skin temperatures of the dorsum of all fingernail folds and the metacarpophalangeal (MCP) joints were measured at baseline. Then the hands were immersed in 10°C wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 14 publications
0
23
0
3
Order By: Relevance
“…Pesquisas apontam recuperação em 10 minutos para grupo controle, sendo a temperatura dos dedos maiores que da região metacárpica [17], [18], [22], [23].…”
Section: Discussionunclassified
“…Pesquisas apontam recuperação em 10 minutos para grupo controle, sendo a temperatura dos dedos maiores que da região metacárpica [17], [18], [22], [23].…”
Section: Discussionunclassified
“…The equipment is relatively expensive and requires regular calibration but technology is advancing and soon thermal cameras may be available as smartphone attachments. Several studies have shown thermography to be able to differentiate between healthy controls and primary Raynaud's and between primary Raynaud's and Raynaud's secondary to systemic sclerosis based upon an abnormal pattern (a persistent "distal-dorsal difference") of rewarming [71,72]. Although thermography as a stand-alone test has some utility, further work may help establish that, in time, assessments of patients with potential CTD may include both a structural assessment in the form of NFC and a functional assessment.…”
Section: Combining Nfc With Other Technologiesmentioning
confidence: 99%
“…Several studies report that IRT can help detect RP [10][11][12]. In healthy subjects, the fingers, especially the finger tips, are usually warmer than the hand.…”
Section: Raynaud's Phenomenonmentioning
confidence: 99%
“…In pRP patients, rewarming is slightly delayed compared to unaffected subjects, while in sRP the hands remain cold for a prolonged time. Some authors, however, question the value of cold challenge, suggesting that baseline thermograms have enough discriminatory power for RP diagnosis [10,15].…”
Section: Raynaud's Phenomenonmentioning
confidence: 99%